2013
DOI: 10.1007/s11205-013-0498-1
|View full text |Cite
|
Sign up to set email alerts
|

A Concept Mapping Study on Social Inclusion in Hong Kong

Abstract: A focus group study involving concept mapping was conducted in September 2012 to investigate how the concept of social inclusion was understood by Hong Kong residents. It was a replication of an earlier UK study. Seven groups involving 61 participants (38 females; 23 males) were interviewed, including non-professional workers at a Nongovernment Organisation service, senior centre users, a mixed group of community residents, people with severe mental illness, professional social service providers, communication… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 16 publications
1
18
0
3
Order By: Relevance
“…Coombs (this volume) reports on the development of a social inclusion measure, using both objective and subjective indicators in the same life domains as Leong (and Chiu) (both this volume) in Singapore, Chan, Evans, Ng, Chiu, and Huxley (2014) in Hong Kong and Huxley et al (2016) in the UK and Warner (1993) in the USA. One of the perceived differences lies in the family life domain, where the family based economic system still prevails in many Eastern societies.…”
Section: Put Itmentioning
confidence: 99%
“…Coombs (this volume) reports on the development of a social inclusion measure, using both objective and subjective indicators in the same life domains as Leong (and Chiu) (both this volume) in Singapore, Chan, Evans, Ng, Chiu, and Huxley (2014) in Hong Kong and Huxley et al (2016) in the UK and Warner (1993) in the USA. One of the perceived differences lies in the family life domain, where the family based economic system still prevails in many Eastern societies.…”
Section: Put Itmentioning
confidence: 99%
“…A concept mapping exercise using focus group interviewing method was conducted to explore the cultural relevancy of social inclusion in Hong Kong. The findings indicated that there were considerable similarities in the understanding of the concept of social inclusion in Hong Kong and the UK (Chan et al, 2013), but with one or two salient differences.…”
Section: Literature Reviewmentioning
confidence: 94%
“…Previous research indicated that interpersonal communication was the main means to promote inclusion and oppose discrimination (Chan et al, ). This is because communication helps people to understand others' points of view and allows their voices and needs to be heard.…”
Section: Literature Reviewmentioning
confidence: 99%